Lifestyle mediates seasonal changes in metabolic health among the yakut (sakha) of northeastern siberia. Issue 6 (13th June 2016) - Levy, Stephanie B.; Leonard, William R.; Tarskaia, Larissa A.; Klimova, Tatiana M.; Fedorova, Valentina I.; Baltakhinova, Marina E.; Josh Snodgrass, J.
ABSTRACT: Objectives: Among indigenous circumpolar populations, extreme seasonality influences food availability and energy metabolism. Furthermore, subsistence patterns and wage labor opportunities shift with season. Thus, health measures among circumpolar populations likely exhibit seasonal changes that are influenced by lifestyle factors. This study examines how markers of cardio‐metabolic health vary between summer and winter as a function of an individual's lifestyle and sex among the Yakut of northeastern Siberia. Methods: Anthropometric dimensions, serum lipids and glucose levels, blood pressure, and lifestyle data were collected for a sample of 115 Yakut participants (71 women, 44 men) in Berdygestiakh, Sakha Republic, Russia in the summer of 2009 and winter of 2011. Results: Men and women experienced significant increases in total and HDL cholesterol and triglyceride levels from summer to winter. Women exhibited winter‐time increases in adiposity and glucose levels. Men who reported greater market integration were more likely to have lower winter blood pressure levels. Additionally, time spent fishing was associated with lower winter‐time LDL cholesterol, while foraging time was associated with higher HDL cholesterol. Conclusions: While seasonal changes in anthropometric dimensions were modest, Yakut men and women experienced significant increases in total cholesterol and HDL cholesterol from summer to winter. These results also suggest that while Yakut individuals with greater subsistence participation are more buffered from adverse seasonal changes in cholesterol levels, they may be at a greater risk for winter increases in blood pressure. Furthermore, the interactions between lifestyle and seasonal change in metabolic health appear to differ between Yakut women and men. Am. J. Hum. Biol. 28:868–878, 2016. © 2016Wiley Periodicals, Inc.